Optimizing Nozzle Geometry of Dry Ice Blasting Using CFD for the Reduction of Noise Emission - Mat, Mohamad Nur Hidayat; Asmuin, Norzelawati (International Journal of Integrated Engineering, 2018)
Dry ice blasting has been used in the modern cleaning industry. However, the primary disadvantage of dry ice blasting is high noise exposure. At a high blasting pressure, the process reaches a harmful noise level of up to 130 dBA [5]. The situation significantly impairs to a human being when the noise emission occurs in an inaudible frequency area. Present safety measures are only based on administrative control by encapsulating the entire system with sound insulationÂ [6]. The main objective of this project is to study the optimum nozzle configuration on the effect of dry ice blasting particle velocity and acoustic noise emission. Ranking and selection [8] method are employed in this study. Several nozzle geometry are simulated until getting the best model for selection. Three-dimension models are designed using CATIA V5. The models are simulated with Ansys Fluent V18.2. The numerical studies have been carried out using density based, standard k-Â e turbulence and Acoustic Broadband Noise Sources model. Six (6) different nozzle configuration namely divergent length, the angle of particle inlet, convergent diameter, expansion ratio, gas inlet diameter and length ratio are analyzed in term of particle velocity magnitude and acoustic power level. The result shows that the optimum nozzle configuration for divergent length, the angle of particle inlet, convergent diameter, expansion ratio, gas inlet diameter and length ratio are 230Â mm, 30 mm, 35 mm, 1.00, 6 mm and 0.80 respectively. This configuration provides minimum acoustic noise emission and maximum particle velocity magnitude.